Clay migration in upland soils of Malaysia - Tessens, E. (British Society of Soil Science, 1984)
Clay movement was studied in a large number of well‐drained soils from Peninsular Malaysia, with a kaolinite mineralogy and an udic or perudic moisture regime. Dispersion in subsoils was found to be related to the net charge on the clay, while in topsoils it was virtually independent of charge or weathering status, and all but one topsoil dispersed well. Accumulation of the dispersed clay is thought to be mainly through flocculation, and as such accounts for the absence of clay coatings in many subsoil horizons. A number of criteria are proposed to distinguish between highly weathered Ultisols and Oxisols, in an effort to improve on the currently used inconclusive properties, such as fine clay to total clay ratio. Copyright © 1984, Wiley Blackwell. All rights reserved